Evaluation of the impact of physical exercise on quality of life and clinical outcomes among women undergoing treatment for breast cancer - Nicole de Moraes Pertile; Juliana Nichterwitz Scherer; Maiara Anschau Floriani; Andriele Abreu Castro; Juçara Gasparetto Maccari; Luiz Antonio Nasi (Brazilian Journal of Oncology)
To evaluate the association between the practice of physical exercises, quality of life and clinical outcomes in women diagnosed with and undergoing treatment for breast cancer. Cohort study, following-up women during 6 months after treatment beginning for breast cancer. A total of 149 participants were recruited for convenience in a private hospital with a specialized service for cancer treatment. Sociodemographic data, practice of physical exercise, duration of exercise per week and domains of quality of life were evaluated through speci?c questionnaires (EORTC-QLQ-C30/EORTC-QLQ-BR23), that aims to measure the following variables: daily tasks, physical, emotional, performance score, pain, fatigue, symptoms, treatment side e?ects, and global health status. The interviews with the patients were carried out during the diagnosis period and after six months of treatment. The average age of the study participants is 58.0 years old [IQ: 44.0-68.0], with the majority of white ethnicity (99.3%). After 6 months of treatment, it has been found that 52.3% of patients (n=78) were practicing some physical exercise. Patients who were practicing exercises during the treatment period had better scores in terms of emotional, social, functional performance, symptoms, global health status and the sum of quality of life scores six months after starting the treatment than those who did not exercise at all (p<0.05). The weekly physical exercise period showed a signi?cant direct correlation with some QoL scores. Finally, the regression analysis showed that women who have practiced physical exercise during treatment had better conditions in terms of physical and daily tasks performance and lower levels of fatigue. Women who have kept regular physical exercises during the treatment for breast cancer have had better health results. Physical exercise is an important activity that should be considered in order to have a healthy routine, as it improves all quality of life domains globally.